2011
DOI: 10.1177/0886260511403745
|View full text |Cite
|
Sign up to set email alerts
|

Describing Intimate Partner Stalking Over Time

Abstract: Stalking has increasingly been the subject of legislation and research in the past 20 years. Within intimate partner violence, the context where it is most likely to occur, stalking predicts both greater danger and greater distress for the victim. However, research shows that practitioners are often unsure how to address stalking, and that the remedies available may not be effective. This longitudinal exploration of stalking focused on the experience of victims of intimate partner stalking and was conducted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…These obstacles might be in the domain of community resources, self-efficacy, or the response (or lack thereof) of others in the survivor's life. Research has been clear that there are no one-size-fits-all solutions for all survivors or even for one survivor over time (Cattaneo, Cho, & Botuck, 2011;Davies et al, 1998;Goodman & Epstein, 2008). Thus the assessment of impact must be ongoing, with the expectation that the effectiveness of actions will shift as other parts of the process and the context of the survivor's life evolves.…”
Section: Impactmentioning
confidence: 99%
“…These obstacles might be in the domain of community resources, self-efficacy, or the response (or lack thereof) of others in the survivor's life. Research has been clear that there are no one-size-fits-all solutions for all survivors or even for one survivor over time (Cattaneo, Cho, & Botuck, 2011;Davies et al, 1998;Goodman & Epstein, 2008). Thus the assessment of impact must be ongoing, with the expectation that the effectiveness of actions will shift as other parts of the process and the context of the survivor's life evolves.…”
Section: Impactmentioning
confidence: 99%
“…Moreover, when the stalker is a woman, underestimating the severity of the event, wherein the perpetrated actions and the consequences experienced by male victims are perceived to be less dangerous, is a greater risk. Cattaneo et al [13] investigation demonstrated the difficulties of male and female victims experience in receiving help from social and health services. Their study, which involved 82 victims interviewed monthly over 7 months, showed that practitioners are often unsure how to address stalking.…”
Section: Introductionmentioning
confidence: 99%
“…A selection was made among the cases of self-declared victimization. The criteria of inclusion were the nature of the relationship [intimate romantic (such as partner and ex-partner) and intimate non-romantic (relatives, close friends – see Spitzberg, 2002 )] and the presence of a form of domestic violence (verbal abuse, physical harm, sexual abuse – Bennett Cattaneo et al, 2011 ). Victims of other types of stalkers (acquaintance, unknown) and those who did not suffer from domestic violence were not included.…”
Section: Introductionmentioning
confidence: 99%